ANALISIS SEKTOR EKONOMI UNGGULAN DAN HUBUNGANNYA DENGAN KESEMPATAN KERJA DAN INVESTASI DI KABUPATEN BATANGHARI - Ahmad Soleh; Hamdi Sari Maryoni (Jurnal Ekonomi-Qu, 2017)
In spurring economic growth, leading sectors have a very central role. Aside from being an effective sector has also become a driving force in developing sectors other sectors. On the basis of the economic sector it is very necessary to analyze the various approaches and theories. The study, entitled "Analysis of Leading Economic Sector in Relation to Employment and Investment in Batang regency" aims to: (1) analyze the sector is a leading sector on the basis Batang regency. (2) analyze the relationship of the flagship sectors with employment opportunities and (3) to analyze the relationship between the leading sectors with investment. This study uses quantitative and qualitative descriptive method using secondary data in the form of time series. The results showed that the sector be seeded based on the analysis of SLQ and services DLQ is the service sector, but all sectors are not specialized. And for the analysis of correlation between the leading sectors (services) with employment showed a positive relationship and a very weak while the relationship of the leading sectors (services services) to the investment is positive and quite strong.On the basis that there should be a good evaluation about development policy, the direction of development, and the development targets so as to accelerate the economic development and welfare.Keywords: seed sector, a sector basis, employment, investment